False Myths versus Medical Facts: Ten Common Misconceptions Related to Dry Eye Disease - Giuseppe Giannaccare; Vincenzo Scorcia (Biomedicines, 2020)
Since the first definition of dry eye, rapid progress has been made in this field over the past decades that has guided profound changes in the definition, classification, diagnosis and management of the disease. Although dry eye is one of the most frequently encountered ocular conditions, various “old” misconceptions persist, in particular among comprehensive ophthalmologists not specialized in ocular surface diseases. These misconceptions hamper the correct diagnosis and the proper management of dry eye in the routine clinical practice. In the present review, we described the 10 most common misconceptions related to dry eye and provided an evidence-based guide for reconsidering them using the format “false myth versus medical fact”. These misconceptions concern the dry eye definition and classification (#1, #2, #3), disease physiopathology (#4), diagnosis (#5), symptoms (#6, #7) and treatment (#8, #9, #10). Nowadays, dry eye is still an under-recognized and evolving disease that poses significant clinical challenges to ophthalmologists. The two major reasons behind these challenges include the heterogeneity of the conditions that fall under the umbrella term of dry eye and the common discrepancy between signs and symptoms.